Effect of Family Resilience Training on the Improvement of Parents’ Knowledge, Skills, and Perceptions in the Kiddos Explorer Community - Ahmad Handayani; Sheila Dhiene Putri; Annisa Mutiara Naulita Siregar; Garsianta Siregar; Muhammad Malik Abdillah Siregar; Ade Andrian; Muhammad Ary Guhtama (UMSU, 2026)
Family resilience training in facing health emergencies and critical situations (K5) is essential to prevent delays in handling emergencies within the household. This study aimed to improve the knowledge, skills, and perceptions of parents in the Kiddos Explorer Medan community regarding family preparedness for emergency situations. The training consisted of two sessions—lecture and practice—covering basic life support (BLS), first aid for wounds, fainting, and choking. A total of 40 parents who met the inclusion criteria and agreed to participate in all sessions were included. Data were collected using pre- and post-test questionnaires across three domains: knowledge, skills, and perception. Statistical analysis was performed using the Wilcoxon Signed Ranks Test. The results showed a significant improvement in all domains (p=0.000). Knowledge increased from a predominantly low category to 45% high, skills improved from 87.5% low to 100% high, and perception rose from 100% moderate to 100% high. These findings indicate that community-based K5 training is effective in enhancing family preparedness for emergencies. This program may serve as a model for strengthening community-based family resilience and can be replicated in other communities.